2012
DOI: 10.1186/1756-8722-5-69
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA inhibits metastasis after palliative resection of hepatocellular carcinoma and prolongs survival in part via vascular normalization

Abstract: BackgroundPromotion of endothelial normalization restores tumor oxygenation and obstructs tumor cells invasion, intravasation, and metastasis. We therefore investigated whether a vasoactive drug, tanshinone IIA, could inhibit metastasis by inducing vascular normalization after palliative resection (PR) of hepatocellular carcinoma (HCC).MethodsA liver orthotopic double-tumor xenograft model in nude mouse was established by implantation of HCCLM3 (high metastatic potential) and HepG2 tumor cells. After removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…These results suggest that Tan IIA may inhibit metastasis (28) possibly through inhibition of HIF-1α/TWIST-induced EMT (14). These results are partially consistent with Wang et al (12) who reported reduced EMT with Tan IIA in an in vivo model of hepatocellular carcinoma. However, similar results were not observed in hypoxic conditions in vitro (12).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results suggest that Tan IIA may inhibit metastasis (28) possibly through inhibition of HIF-1α/TWIST-induced EMT (14). These results are partially consistent with Wang et al (12) who reported reduced EMT with Tan IIA in an in vivo model of hepatocellular carcinoma. However, similar results were not observed in hypoxic conditions in vitro (12).…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with Xu et al (26) who reported that Tan IIA reduced LPS-induced sepsis syndrome through targeting HIF-1α. However, in hepatocellular carcinoma cells, HIF-1α levels were not altered with Tan IIA in hypoxic conditions in vitro (12).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Fu et al [18] have found that Tan ⅡA blocks EMT in MCF-7 and HCC1973 breast cancer cell lines Q5 . Likewise, Wang et al [19] have reported that Tan ⅡA inhibits EMT and metastasis of hepatocellular carcinoma in vivo. These two previous lines of evidence indicate an inhibitory effect of Tan ⅡA on EMT of breast and liver cancer cells.…”
Section: Introductionmentioning
confidence: 96%
“…If promotion of blood circulation was used alone, it would not have triggered cancer cell metastasis. Indeed, it was demonstrated that improving blood circulation reduced cancer metastasis (45). However, the problem with using Chinese medicine to promote blood circulation alone, is that it would be difficult to detect a tumor size reduction or disappearance; this may be difficult for physicians and patients to accept.…”
Section: Promotion Of Blood Circulation Vs Metastasismentioning
confidence: 99%